Features of Psychophysiological Adaptation of Foreign Students in Medical Universities: Características de la Adaptación Psicofisiológica de los Estudiantes Extranjeros en las Universidades de Medicina - Chonkoeva, Aigul; Taalaibekova, Ykyval; Zhaparalieva, Cholpon; Mannap uulu, Nurlanbek; Chonkoeva, Aikerim (Gaceta Médica de Caracas, 2025)
Introduction: Psychophysiological adaptation of foreign medical students is a pressing issue due to the increasing influx of students from abroad. Objective: This study aimed to identify the factors affecting the adaptation of international students in the process of studying at medical universities of the Kyrgyz Republic, with a special focus on climatic conditions, study load, and stress factors. Method: The study was conducted from 2022 to 2023 at Ala-Too International University and the International Graduate School of Medicine, involving 150 first-year students from India and Pakistan. The analysis of data obtained from questionnaires, physiological tests, and biochemical analyses revealed significant changes in levels of anxiety, stress tolerance, and physiological indicators such as cortisol levels, blood pressure, and heart rate, as well as the state of the respiratory system.